Structural change in the US Phillips curve, 1948-2021: The role of power and institutions - Mark Setterfield; Robert A. Blecker (Hans-Böckler-Stiftung, Macroeconomic Policy Institute (IMK), Forum for Macroeconomics and Macroeconomic Policies (FMM), 2022)
This paper provides an institutional-analytical account of changes in the structure of the US Phillips curve (PC) during the post-war period. It does so by restoring conflict and power to the forefront of macro theory and, in particular, the wage- and price-setting behaviour of workers and firms. The resulting account is consistent with the main stylized facts that characterize the evolution of the US PC since 1948: the disappearance and subsequent reappearance of a 'standard' PC (relating the level of the inflation rate, not the change in this rate, to the rate of unemployment); and the flattening of the PC since the 1990s.
Keywords: E12; E24; E25; E31; N12; 330; Phillips Curve; inflation; unemployment; natural rate hypothesis; bargaining power; institutions